Prevalence and Impact of Central Post-Stroke Pain on Quality of Life Among Stroke Survivors: A Cross-Sectional Study - Sekplin A.S Sekeon; Asri Adisasmita; Mondastri K Sudaryo; Aida R Tantri (Acta Medica Indonesiana)
Background: Stroke continues to be a significant public health challenge. Central post-stroke pain (CPSP) is a notable aspect of post-stroke pain that not only causes physical discomfort but also affects psychological well-being, leading to a reduced quality of life. The objective of this was to assess the prevalence of CPSP and its relationship with quality of life. Methods: This hospital-based cross-sectional study was conducted between August and December 2023 in Manado, Indonesia, the study involved the consecutive recruitment of stroke patients. CPSP diagnosis adhered to the 2017 criteria set forth by the American Pain Society, while quality of life was evaluated using the Indonesian version of the Stroke Specific Quality of Life (SS-QoL) scale. Results: The study comprised 166 stroke patients, revealing that 30.1% experienced CPSP. Notably, there was a significant difference in mean SS-QoL scores based on both the severity of the stroke and the presence of depression. Within the CPSP group, a significant variation in SS-QoL summary scores was observed between male and female patients. Those with CPSP reported significantly lower mean scores in the Thinking and Energy categories. However, there was no significant difference in the overall SS-QoL scores between CPSP and non-CPSP patients. Conclusion: In summary, stroke patients suffering from depression, greater severity of stroke, and those experiencing burning or pressure-like sensations are at an increased risk of having a lower quality of life.